Impact of ICT in organizational communication (2017)
This paper analyzes the impact of the substantial implementation of ICT information and communication technologies in the communicative processes within the organizations, answering the question What changes have been generated with the implementation of ICT in the processes of Communication within organizations? It describes ICT in organizational communication as a fundamental part of the development of corporate activities and analyzes its importance. It contrasts briefly the levels of productivity before and after the implementation of ICT in companies.